Contemporary Canadian Picture Books - Brenna, Beverley (Critical New Literacies: The Praxis of English Language Teaching and Learning, 2021)
This enriched reference guide offers a unique overview of more than 200 picture books published by Canadian publishing houses between 2017–2019. The authors cover key themes in contemporary Canadian titles that match broad curriculum trends in education. Response activities are included in the text, for example frameworks for critical literacy discussions, along with annotated bibliographies that specifically recognize titles by Indigenous authors and illustrators. The book also contains original interviews with a dozen rising stars in Canadian writing and book illustration. While the book is specifically geared for educators, it also supports public libraries, Education researchers, and future picture book creators, as well as families who are interested in learning more about reading development and related literacy activities for the home setting. Readership: This book is a welcome contribution to education research and practice. It has a market among all those professionally interested in Canadian children’s literature, and also for families interested in literacy development.